EFFECT OF PART TRANSFER POLICIES IN TWO TYPES OF LAYOUTS IN AUTOMOTIVE BODY SHOPS - Moon, Dug Hee; Nam, Ye Seul; Kim, Ha Seok; Shin, Yang Woo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Body shop in an automotive factory consists of many sub-lines which are highly automated transfer line, and the sub-lines are merged in many assembly operations. <span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">To design a body shop, the layout concepts based on welding technologies and the material handling systems should be considered and optimized. Two types of layout concepts are widely used, and they are called as the layered build layout and the modular build layout. <span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">There are <span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">also <span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">two part transfer policies in a transfer line with unreliable machines and no buffer. The first transfer policy<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US"> is the asynchronous transfer which<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> allows a part move to the next operation independently<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">. T<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">he second policy <span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">is the synchronous transfer which <span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">allows part<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">s<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> move to the next operation whenever all operations in a sub-line finish their operations. In this <span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">study<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> we compare two types of transfer policies in two different <span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">layouts having<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> many transfer lines<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US"> and assembly operations<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">in automotive body shops<span style="font-family: ’Times New Roman’,’serif’; font-size: 10pt; mso-fareast-font-family: 바탕; mso-font-kerning: 0pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> by simulation study.